Spatial accessibility analysis of green space from a health-benefit perspective: Implications for healthy urban development - Wei, Xiangrui; Zhao, Chunrong; Yan, Li; Fu, Juanlin; Bao, Ying; Liu, Xiao (Frontiers in Ecology and Evolution, 2022)
Spatial accessibility of urban park green space (UPGS) plays a crucial role in promoting the healthy development of cities and residents. However, studies have inadequately considered the impact of variegated parks on residents' needs, overestimating UPGS accessibility. First, we proposed an improved two-step floating catchment area (Huff-2SFCA) method that considers the trade-offs of supply, demand, and walking time to calculate the UPGS accessibility index in the built-up area of Mianyang, China. Next, we assessed the spatial characteristics of UPGS accessibility from a partial and overall viewpoint and further explored the relationship between accessibility and population size. The results showed that (1) every street area has a different construction of UPGS, and most of those spaces have poor quality; (2) municipal-level parks are significantly more accessible than district-level parks, community-level parks, and neighborhood-level parks; (3) the overall accessibility distribution is generally characterized by a decreasing trend along both sides of the river, with poor accessibility overall; and (4) 243 residential districts are located in high demand-low supply areas that need be improved. This study can be employed to identify areas underserved by UPGS and provide a basis for improving accessibility and promoting the health benefits of UPGS.